Cytocompatible Fabrication of Yeast Cells/Fabrics Composite Sheet for Bioethanol Production. Issue 20 (26th June 2018) - He, Bin; Zhu, Xing; Zhao, Changwen; Wang, Guan; Ma, Yuhong; Yang, Wantai
Abstract: Entrapment of living cells into a polymer network has significant potential in various fields such as biomass conversion and tissue engineering. A crucial challenge for this strategy is to provide a mild enough condition to preserve cell viability. Here, a facile and cytocompatible method to entrap living yeast cells into a poly(ethylene glycol) (PEG) network grafting from polypropylene nonwoven fabrics via visible‐light‐induced surface living graft crosslinking polymerization is reported. Due to the mild reaction conditions and excellent biocompatibility of PEG, the immobilized yeast cells could maintain their viability and proliferate well. The obtained composite sheet has excellent long‐term stability and shows no significant efficiency loss after 25 cycles of repeated batch bioethanol fermentation. The immobilized yeast cells exhibit 18.0% higher bioethanol fermentation efficiency than free cells. This strategy for immobilization of living cells with high viability has significant potential application. Abstract : Living cells are entrapped into a poly(ethylene glycol) network grafted on polypropylene fabric by visible‐light‐induced graft polymerization.